Barriers and enablers to collaboration in the mental health system in Sabah, Malaysia: towards a theory of collaboration. Issue 1 (January 2020) - Shoesmith, Wendy; Awang Borhanuddin, Awang Faisal Bin; Pereira, Emmanuel Joseph; Nordin, Norhayati; Giridharan, Beena; Forman, Dawn; Fyfe, Sue
Abstract : Background: The systems that help people with mental disorders in Malaysia include hospitals, primary care, traditional and religious systems, schools and colleges, employers, families and other community members. Aims: To better understand collaboration between and within these systems and create a theoretical framework for system development. Method: A total of 26 focus groups and 27 individual interviews were undertaken with patients, carers, psychiatric hospital staff, primary care and district hospital staff, religious and traditional healers, community leaders, non-governmental organisation workers, and school and college counsellors. Grounded theory methods were used to analyse the data and create a theory of collaboration. Results: Three themes both defined and enabled collaboration: (a) collaborative behaviours; (b) motivation towards a common goal or value; and (c) autonomy. Three other enablers of collaboration were identified: (d) relatedness (for example trusting, understanding and caring about the other); (e) resources (competence, time, physical resources and opportunities); and (f) motivation for collaboration (weighing up the personal costs versus benefits of acting collaboratively). Conclusions: The first three themes provided a definition of collaboration in this context: 'two or more parties working together towards a common goal or value, while maintaining autonomy'. The main barriers to collaboration were lack of autonomy, relatedness, motivation and resources, together with the potential cost of acting collaboratively without reciprocation. Finding ways to change these structural, cultural and organisational features is likely to improve collaboration in this system and improve access to care and outcomes for patients.